PENGGUNAAN PREPOSISI TETAP BAHASA BELANDA OLEH MAHASISWA PROGRAM STUDI BELANDA SEMESTER 3 DAN 5 TAHUN AJAR 2024/2025 - Rosprianti, Caesi; Gustinelly, Eliza (Multikultura, 2025)
This study examines the use of fixed prepositions in Dutch by third- and fifth-semester students of the Dutch Studies Program in the academic year 2024/2025. The topic of this research is related to linguistics, specifically grammar and vocabulary. The theoretical framework used in this study is the meaning of fixed prepositions by Van den Toorn, Willy Vandeweghe, and Walter Haeseryn. et al. This research employs a descriptive method with a quantitative approach to analyze the extent of third- and fifth-semester students' ability in answering questions related to the use of fixed prepositions, classified according to their association with verbs, adjectives, and nouns. The data for this study were collected from the completion of questions about fixed prepositions by 10 third-semester students and 10 fifth-semester students from the Dutch Studies Program in the academic year 2024/2025. The results of this study show that fifth-semester students have a better command of using fixed prepositions in relation to verbs, adjectives, and nouns compared to third-semester students.